Pengaruh Current Ratio Dan Return On Asset Terhadap Return Saham Pada PT Bank Rakyat Indonesia (Persero) Tbk - Mappamiring, Mappamiring; Sukarno, Zulfikry (Universitas Dian Nuswantoro, 2023)
The objective of the research is to determine the influence of the current ratio and return on assets on stock returns at PT Bank Rakyat Indonesia (Persero) Tbk. Research data comes from Financial Reports for 10 years from 2012 to 2021 obtained from www.bri.co.id and www.idx.co.id. The descriptive quantitative research approach method is the results of SPSS v.25 statistical analysis in the form of numbers and then described in the form of an explanation of the results of scientific research. Based on the results of the t-test, it is known that the current ratio has no effect on stock returns with a calculated t value of -0.544 < t table 2.026 and a probability value of 0.590 > 0.05. And the return on assets variable also does not have a significant effect on stock returns. With a t-count value of 1,327 < t table 2,026 and a probability value of 0.193 > 0.05.